2016
DOI: 10.1111/nmo.12865
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic nervous system function predicts the inflammatory response over three years in newly diagnosed ulcerative colitis patients

Abstract: This study further strengthens the association between the ANS system and intestinal inflammation previously found in animal models and recently in patients with inflammatory bowel disease. These results may have important implications for the pathogenesis and treatment of UC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 32 publications
(78 reference statements)
1
19
0
Order By: Relevance
“…Besides, AMY1 gene copy number was comparable between UC patients and controls. Our findings might implicate an altered ANS activity in UC patients, which was consistent with previous studies [ 15 17 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Besides, AMY1 gene copy number was comparable between UC patients and controls. Our findings might implicate an altered ANS activity in UC patients, which was consistent with previous studies [ 15 17 ].…”
Section: Discussionsupporting
confidence: 93%
“…In humans, the attempts to identify whether ANS alterations are present in UC has not come to a conclusion on the relationship between ANS function and UC disease activity. Nevertheless, a couple of previous studies had demonstrated altered ANS activities in UC patients [ 15 17 ], especially an elevated sympathetic nervous activity in this population [ 15 , 16 ]. In the current study, we detected an elevated sAA secretion before and after gustatory stimulation, which also indicated an elevated sympathetic nervous activity in UC patients.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…One explanation for the differences between UC and CD subtypes is that CD can affect any part of the GIT, whereas UC predominantly occurs in the distal colon and rectum, areas that are not innervated by the vagus nerve 3 . Nevertheless, a negative association between parasympathetic activity and inflammation parameters has also been reported in UC, although it remains unclear to what extent the vagus nerve is involved 10 …”
Section: Discussionmentioning
confidence: 99%
“…Pellissier et al have showed that CD patients with low parasympathetic vagal tone demonstrate higher blood tumour necrosis factor alpha (TNF‐α) levels than patients with high vagal tone 9 . Moreover, sympathovagal balance has been correlated with TNF‐α levels in UC and higher parasympathetic tone at onset of UC predicts lower systemic inflammation during the next 3 years 10 …”
Section: Introductionmentioning
confidence: 99%